Neighbourhood social environment on physical activity among adults in Sri Lanka: a qualitative inquiry - Shreenika De Silva Weliange; Dulitha Fernando; Jagath Gunatilake (College of Community Physicians of Sri Lanka, 2018)
Background: Adopting an active lifestyle is a complex behavioural process, which is influenced by various factors. Social environment characteristics are well recognized to influence health and physical activity (PA) behaviour. However, social environment appears to be the least studied area of PA. Objective: To assess the social environment and its association with PA in Sri Lanka Methods: A qualitative methodology was used. We conducted 6 focus group discussions among 58 adult residents, using a guide to facilitate the discussions and to collect the information. Purposive sampling was carried out to gather participants from areas differing in the level of urbanicity. Results: Majority of the participants in the focus group discussions were females (51.7%) and many had secondary level education. Healthy social interactions and networks and unity and respect for person in a community were seen to facilitate PA. Undesired behaviour in the community hindered youth and women in being active especially at recreational places (playing sport or exercising) and on the roads (walking for leisure and transport). Attitudes and beliefs were also identified. The reasons for these social attitudes were due to lack of proper knowledge, the socio-economic gap and lack of policies for social equality. Conclusions: Social environment is an important factor in promoting PA in Sri Lanka and needs to be addressed when planning to promote active living.